2022
DOI: 10.3389/fmicb.2021.797062
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Effect of Atorvastatin: Akkermansia muciniphila and Barrier Function

Abstract: Studies have shown that the cholesterol-lowering medicine statins alter the gut microbiome, induce chronic metabolic inflammation, and disrupt glycemic homeostasis. In this study, we aimed to investigate whether effects of atorvastatin (Ator) on gut microbiome and metabolic inflammation could be causally correlated. Mice at 8-week age were fed with high-fat diet (HFD) or HFD with Ator (HFD+Ator) for 16 weeks. 16S rRNA sequencing of stool and RNA sequencing of colon tissue were employed to analyze the intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Lv et al 10.3389/fcimb.2022.957439 In recent years, the geographic deviation among different subspecies has been described in several gut bacteria such as Prevotella copri (Tett et al, 2019) and Eubacterium rectale (Karcher et al, 2020). These findings suggested that not only the geographical factor but also other unknown factors (e.g., diet difference between populations (Cheng et al, 2021;Dıéz-Sainz et al, 2022), or movement of individuals) are probably the forces for speciation of the gut bacteria. Similarly, except for Amuc III, Amuc I, II, and IV were observed in the gut microbiota of American children in the study of Kirmiz et al (2020).…”
Section: Global Distribution Of Akkermansia Phylogroupsmentioning
confidence: 99%
“…Lv et al 10.3389/fcimb.2022.957439 In recent years, the geographic deviation among different subspecies has been described in several gut bacteria such as Prevotella copri (Tett et al, 2019) and Eubacterium rectale (Karcher et al, 2020). These findings suggested that not only the geographical factor but also other unknown factors (e.g., diet difference between populations (Cheng et al, 2021;Dıéz-Sainz et al, 2022), or movement of individuals) are probably the forces for speciation of the gut bacteria. Similarly, except for Amuc III, Amuc I, II, and IV were observed in the gut microbiota of American children in the study of Kirmiz et al (2020).…”
Section: Global Distribution Of Akkermansia Phylogroupsmentioning
confidence: 99%
“…Further complexity in the interpretation of urinary adipokine levels may arise from the fact that their serum concentrations can differ between sexes and are often related to BMI and metabolic diseases [ 2 , 21 , 48 , 50 , 151 , 165 , 226 ]. Commonly used drugs such as atorvastatin may promote intestinal barrier dysfunction and may also affect fecal and urinary protein levels [ 227 ]. However, how these parameters may influence urinary or fecal adipokine levels has not yet been thoroughly analyzed, and further research is required to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that long-term fed with high fat diet may alter gut microbiota, induce intestinal barrier dysfunction, and hence promote chronic inflammation that contributes to disrupted glycemic homeostasis ( He et al, 2020 ; Ahrens et al, 2021 ; Cheng et al, 2021 ). GP as one of the constituent drugs of XZP, reduced the Firmicutes/Bacteroidetes ratio ( Li S. et al, 2022 ), enriched the abundance of Lactococcus spp.…”
Section: Discussionmentioning
confidence: 99%